PUBLIC POLICIES ON INFORMATION AND COLLECTIVE INTELLIGENCE: the challenges and possibilities for the democratization of information - Franco, Angela Haien Clam; Carvalho, Angela Maria Grossi [UNESP]; Amorim da Costa Santos, Placida Leopoldina Ventura [UNESP] (Univ Federal Campina Grande, 2019)
The social information paradigm presents multiples challenges for the interactive knowledge time of Information Science, especially whit regard to the use of collective intelligence in digital environments. In this context, the collective intelligence manifests itself as a proposal that aims at harnessing individual skills for the development of a Knowledge space. The provision of technological infrastructure and digital competences for the insertion of individuals in this space requires the establishment of efficient public policies for the information area. Therefore, through the exploratory and descriptive analysis, it is intended to bring information policies closer to collective intelligence. It was observed that ideals of democratization of information was common to both fields, and that defining consistent public information polices is viable alternative for the realization of the Knowledge space, and consequently for the valorization of collective intelligence.
Keywords: Collective intelligence; Public policies; Information public policies; Information and communication technologies